NOD2 Expression in Streptococcus pneumoniae Meningitis and Its Influence on the Blood-Brain Barrier - Ying Wang; Xinjie Liu; Qi Liu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Streptococcus pneumoniae meningitis is one of the most common disorders seen in clinical practice. It is believed that the brain tissue immune injury is caused by the expression of pattern-recognition receptors (PRR) which can further induce the release of other cytokines and inflammatory cascades. The aim of this study is to investigate the expression of nucleotide-binding oligomerization domain 2 (NOD2) and inflammatory factors in rat brain tissues infected with Streptococcus pneumoniae and its influence on the blood-brain barrier (BBB) permeability. Rats were given an intracranial injection of Streptococcus pneumoniae to construct the Streptococcus pneumoniae meningitis rat models. The expression change curves of NOD2 and inflammatory factors at different time points (0 h, 12 h, 24 h, 48 h, and 7 d) after Streptococcus pneumoniae were evaluated by enzyme-linked immunosorbent assay (ELISA). Western blotting analysis and quantitative real-time polymerase chain reaction (qRT-PCR) were engaged to examine the expression of NOD2. Furthermore, the changing processes of pathological characteristics, nervous system score, cerebral oedema, and BBB permeability were observed. Our results showed that NOD2 expression began to increase in the 12 h after Streptococcus pneumoniae infection group, while the remaining inflammatory factors were not obviously increased. Meanwhile, the levels of NOD2, as well as inflammatory factors IL-1β, TNF-α, and IL-6 were markedly elevated in 24 h and 48 h infection groups, which were consistent with the increases in BBB permeability and BWC, and the positive expression of NOD2 in the infected rat brain tissues was observed using immunohistochemistry (IHC). This study suggests that NOD2 might be related to the activation of inflammation pathways and the damage to the blood-brain barrier. NOD2 and inflammatory factors have played vital roles in the pathogenesis of Streptococcus pneumoniae meningitis.